CEOs and the Product Market: When Are Powerful CEOs Beneficial? - Li, Minwen; Lu, Yao; Phillips, Gordon M. (Journal of Financial and Quantitative Analysis, 2019)
We examine whether industry product market conditions are important in assessing the benefits and costs of chief executive officer (CEO) power. We find that firms are more likely to have powerful CEOs in high demand product markets where firms are facing entry threats. In these markets, investors react favorably to announcements granting more power to CEOs, and CEO power is associated with higher market value, sales growth, investment, advertising, and the introduction of more new products. Our results remain significant when addressing the endogeneity of CEO power by instrumenting CEO power with past non-CEO executive and director sudden deaths.